FAMILY BUSINESS "FROM HOME ONLY" DURING THE COVID-19 OUTBREAK IN INDONESIA: PROSPECTS AND STRATEGIES - Jaelani, Aan; Yusuf, Ayus Ahmad; Layaman, Layaman; Aziz, Abdul; Rokhlinasari, Sri (Cirebon International Journal of Economics and Business, 2025)
This article will explore the spread of COVID-19 which has an impact on the family economy in Indonesia. The lack of literature on family businesses during the economic crisis caused by the Coronavirus outbreak shows that this study is very important for family-run businesses. Business opportunities and prospects remain open to every family, but this requires a change in strategy in managing its business that is facing changes in work culture and the community's first choice in meeting needs. The qualitative method was used to read the initial phenomena about the family economic and business conditions of the COVID-19 in Indonesia with secondary data sources from reputable international publications, the Task Force for the Acceleration of Handling COVID-19 of Indonesian and WHO Coronavirus Disease, and the ideas of business practitioners. The conclusion of this paper is that the prospects of a family-run business are very open and even have the opportunity to succeed in the COVID-19 period by carrying out basic intervention dimensions that support smart, sustainable, and inclusive growth in family businesses: survival and longevity, firm growth, innovation, internationalization, and entrepreneurship.